2011
DOI: 10.1039/c0jm04185h
|View full text |Cite
|
Sign up to set email alerts
|

The nano-branched structure of cementitious calcium–silicate–hydrate gel

Abstract: Manipulation of concrete at the nanoscale is severely limited by the lack of precise knowledge on the nanostructure of calcium-silicate-hydrate gel, the main binding phase of cement-based materials. Here we report a computational description of C-S-H, which for the first time reconciles the existing structural and colloidal/gel-like models. Our molecular dynamic simulations predict the formation of a branched three-dimensional C-S-H solid network where the segmental branches (SB) are $3 Â 3 Â 6 nm-sized. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
3
53
1
Order By: Relevance
“…Second, the globule disk radius R increases in samples with additives of PCE23-2 and PCE102-6. This means that when adding PCE23-2 and PCE102-6, the microstructure of CÀSÀH becomes more like the continuous extension of branched or interconnected multi-lamellar sheets, as in the models proposed by Dolado et al [17,18] and McDonald et al [19]. In addition, by fitting the SAXS data with IðQ Þ ¼ C p  Q À4 in the range of 0.23 Å À1 < Q < 0.29 Å À1 , where the contribution from S(Q) is negligible, we found that the Porod constant C p (not shown), which is proportional to the total surface area per volume, has the trend: CÀSÀH > CÀSÀH/PCE102-2 > CÀSÀH/PCE23-6 > CÀSÀH/PCE23-2 > CÀSÀH/PCE102-6.…”
Section: Resultsmentioning
confidence: 86%
“…Second, the globule disk radius R increases in samples with additives of PCE23-2 and PCE102-6. This means that when adding PCE23-2 and PCE102-6, the microstructure of CÀSÀH becomes more like the continuous extension of branched or interconnected multi-lamellar sheets, as in the models proposed by Dolado et al [17,18] and McDonald et al [19]. In addition, by fitting the SAXS data with IðQ Þ ¼ C p  Q À4 in the range of 0.23 Å À1 < Q < 0.29 Å À1 , where the contribution from S(Q) is negligible, we found that the Porod constant C p (not shown), which is proportional to the total surface area per volume, has the trend: CÀSÀH > CÀSÀH/PCE102-2 > CÀSÀH/PCE23-6 > CÀSÀH/PCE23-2 > CÀSÀH/PCE102-6.…”
Section: Resultsmentioning
confidence: 86%
“…This could provide more insights into the connection between gels and gas-liquid behavior of colloidal systems. We would like to extend our model to study physical systems like Janus particles but also the formation of calcium-silicate-hydrate (CSH) gels formed during cement hydration [88]. In the later case, it could be interesting to mix an aggregation process with the nucleation and growth of the basic building blocks of CSH gels [89].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] In addition, models and simulations have been developed to enhance understanding and materials design. 8,10,[19][20][21][22][23][24][25][26][27][28][29][30] Such approaches include electronic structure calculations, molecular dynamics, Monte Carlo, and continuum methods, as well as multi-scale combinations of methods.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of actual nanocrystals, aqueous interfaces, surface reactions, selective adsorption of organic modifiers, and assembly of nano-objects thus require classical molecular dynamics simulations and Monte Carlo simulations. 8,10,19,23,24 Such models on the basis of force fields retain all-atomic detail for up to a million atoms and access time scales up to microseconds. Simulation of yet larger systems of micrometersize particles, grinding, sedimentation, and aggregate mechanical properties is feasible using coarse-grain and continuum methods.…”
Section: Introductionmentioning
confidence: 99%